Network reconfiguration for enhancement of voltage stability in distribution networks - Kashem, M. A.; Ganapathy, V.; Jasmon, G. B. (2000)
Network reconfiguration is performed by altering the topological structure of distribution feeders. By reconfiguring the network, voltage stability can be maximised for a particular set of loads in distribution systems. A new algorithm is formulated for enhancement of voltage stability by network reconfiguration. Initially, a certain number of switching combinations is generated using the combination of tie and its two neighbouring switches, and the best combination of switches for maximising the voltage stability in the network among them is determined. Then the search is extended by considering the branches next to the open-branches of the best configuration one by one to check whether there is any other switching combination available which gives further improvement in voltage stability. The enhancement of voltage stability can be achieved by the proposed method without any additional cost involved for installation of capacitors, tap-changing transformers and the related switching equipment in the distribution systems. The method has been tested on a 69-bus test system, and the results indicate that it is able to determine the appropriate switching options of the optimal (or near optimal) configuration for voltage stability enhancement with less computation. It has also been shown that power losses are reduced when voltage stability is improved by network reconfiguration.